EFEKTIVITAS STRATEGI WEBINAR DALAM EDUKASI PENYULUHAN TENTANG KEBIJAKAN INSENTIF PERPAJAKAN DI MASA PANDEMI COVID-19 TERHADAP PARTISIPASI WAJIB PAJAK - Ratih Frayunita Sari; Santoso, Dwi Langgeng (Scientax, 2021)
The COVID-19 pandemic has had a major domino effect on industrial economies. Various policies and strategies are carried out by the government, one of the concrete steps is by issuing incentive and relaxation policies in the field of taxation for taxpayers. The Directorate General of Taxation (DGT) has the task of providing information dissemination on taxation and the current condition of COVID-19 has brought transformation to a webinar. This strategy is carried out to keep providing information and education on tax relief. This study aims to identify the extent of the influence of the webinar strategy on taxpayer participation. The sample technique in this study was purposive sampling and obtained 307 respondents who participated in the DJP webinar. This research uses a Computer Mediated Communication (CMC) theoretical approach to see the communication process of participants and speakers in a communication technology-based webinar. From the research results, it was found that there was a significant influence in the use of webinars. This is shown from the aspect of system quality, quality of information, service quality from webinars through the Zoom Meeting application, thereby increasing taxpayer participation.